2016
DOI: 10.1038/srep24024
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Insulin Signaling Encodes Two Different Molecular Mechanisms for the Shortened Longevity Induced by Graphene Oxide in Caenorhabditis elegans

Abstract: Graphene oxide (GO) has been shown to cause multiple toxicities in various organisms. However, the underlying molecular mechanisms for GO-induced shortened longevity are still unclear. We employed Caenorhabditis elegans to investigate the possible involvement of insulin signaling pathway in the control of GO toxicity and its underlying molecular mechanisms. Mutation of daf-2, age-1, akt-1, or akt-2 gene induced a resistant property of nematodes to GO toxicity, while mutation of daf-16 gene led to a susceptible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 44 publications
(83 reference statements)
2
21
0
Order By: Relevance
“…Strikingly, egg‐laying and body size were the only parameters that were changed upon chronic exposure, while developmental timing, pharyngeal pumping, locomotion, and lifespan (bagging animals were censored from the population) stayed unaffected, which stands in contrast to previous GO toxicity studies in C. elegans . This discrepancy can be explained by differences between the physicochemical characteristics of GO, which has half the lateral size as compared to our study.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Strikingly, egg‐laying and body size were the only parameters that were changed upon chronic exposure, while developmental timing, pharyngeal pumping, locomotion, and lifespan (bagging animals were censored from the population) stayed unaffected, which stands in contrast to previous GO toxicity studies in C. elegans . This discrepancy can be explained by differences between the physicochemical characteristics of GO, which has half the lateral size as compared to our study.…”
Section: Resultssupporting
confidence: 66%
“…Stress response mechanisms, including signaling pathways that regulate the innate immune response, are well‐conserved in C. elegans , and protect the animals from environmental stress, pathogens, viruses, toxins and heavy metals, making the worm a powerful model for complex human diseases . In recent years, the possible adverse effects of graphene on C. elegans have been investigated, resulting in considerable variations between the studies when measuring fecundity, development and lifespan, which might depend on the differences between the GO synthesis protocols and the specific treatment paradigm …”
Section: Introductionmentioning
confidence: 99%
“…Exposure to GO could also induce cytotoxicity by activating the genuine autophagy35. Our previous studies in C. elegans have suggested that the insulin, JNK, apoptosis, and DNA damage signaling pathways are also involved in the control of GO toxicity242526. In this study, we observed that exposure to GO could affect the expression patterns of three Wnt ligands, CWN-1, CWN-2, and LIN-44, in nematodes (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…A few important signaling pathways, including insulin, c-Jun N-terminal kinase (JNK), apoptosis, and DNA damage signaling pathways have already been shown to be involved in the control of GO toxicity in nematodes242526. The Wnt signaling pathway is one of the evolutionarily conserved signal transduction pathways, and is extensively utilized during the development of animals and humans27.…”
mentioning
confidence: 99%
“…However, in a recent report, reduced graphene oxide (r‐GO) nanosheets showed little change in exploratory, anxiety‐like, or learning and memory behaviors, although general locomotor activity, balance and neuromuscular coordination were initially affected in mice (Zhang et al, ). A series of studies have suggested that nanomaterials elicit toxicity to C. elegans (Wang, ; Yang et al, ; Zhao et al, ). Wu et al () also observed a significant decrease in locomotion behavior in 10–100 mg l −1 GO‐exposed nematodes as reflected by endpoints of head thrash and body bend (Wu et al, ).…”
Section: Discussionmentioning
confidence: 99%